Prevalence and Correlates of Prescription Drug Misuse Among a Racially Diverse Sample of Young Sexual Minority Men - Li, Dennis H. (LGBT Health, 2018)
Purpose: Sexual minority men (SMM) are at greater risk than heterosexual men for misusing prescription psychotropic medications. However, community prevalence estimates of prescription drug misuse among young SMM are lacking. The current study described lifetime and past-6-month stimulant, painkiller, and depressant/tranquilizer misuse in a large, racially diverse sample of 967 SMM aged 16–29 in Chicago, Illinois, and investigated demographic and other substance use associations. Methods: Data came from the baseline visit of the RADAR longitudinal cohort study. Associations were examined using bivariate and multivariable logistic regression. Results: A quarter of the sample reported ever misusing any prescription drug, and 14.2% reported recent misuse. Lifetime class-specific misuse was 16.9% for stimulants, 11.0% for painkillers, and 11.4% for depressants/tranquilizers; recent misuse was 8.0%, 5.7%, and 6.2%, respectively. In multivariable analysis, Non-Hispanic black participants had lower odds of lifetime stimulant and depressant/tranquilizer misuse and recent stimulant misuse than non-Hispanic white participants, and bisexual participants had greater odds of lifetime and recent painkiller and depressant/tranquilizer misuse than gay participants. Generally, using other substances was associated with greater odds of prescription drug misuse. Having ever been prescribed a psychotropic medication was associated with higher odds of lifetime painkiller misuse after controlling for covariates. Conclusion: These results provide critical information on a growing public health problem among young SMM. Future research should explore why differential rates of misuse exist across subgroups. New interventions emphasizing the risk of prescription drugs, discouraging drug sharing, and bolstering refusal and coping skills should be developed and evaluated.